Remediation of an Organochlorine Compound in an Unsaturated Zone Using a DL-Limonene Microemulsion System - Campos, V. [UNESP]; Marques, D. G. [UNESP]; Anjos, D. N. [UNESP] (Croatian Society of Chemical Engineers/HDKI, 2022)
Contamination of the unsaturated zone, and hence, of groundwater by non-aqueous phase liquids has become a problem that arouses great concern due to the environmental damage it causes. Several efficient and economically beneficial techniques for the in situ treatment of contaminated soils have been applied quite frequently, including the so-called soil flushing processes. In this study, microemulsion systems were prepared using limonene, in the search for a formulation that would remove trichloroethene in soil. Limonene, a monocyclic monoterpene, is one of the main constituents of various essential oils of citrus fruits, such as oranges, tangerines and lemons. The results indicated that using a washing fluid containing 15 % DL-limonene microemulsion enabled the removal of 98.85 % of trichloroethene present in the soil after 30 minutes of residence time in the system. Hence, it can be concluded that the use of this microemulsion system is an interesting strategy for the remediation of soils contaminated with trichloroethene.
Keywords: contaminated soil; DL-limonene microemulsion; remediation; trichloroethene